Ketidaksesuaian Maksim Kuantitas pada Kolom Komentar Berita Online CNN di Instagram - Nur Khasanah, Dwi Faradylla; Sri Wahono Saptomo; Pardyatmoko; Sukarno (Kajian Linguistik dan Sastra, 2025)
The effectiveness of communication in digital discussions still faces various challenges. One of them isin the comment column on social media platforms such as Instagram which is often a space forinconsistencies in the maxim of quantity in communication. This study aims to provide a description ofthe forms of non-compliance with the maxim of quantity in online news commentary as well as thefactors that influence it. The method used in this study is qualitative descriptive. The source of the datacomes from the comment column on the post uploaded on October 20, 2024, the Instagram accountsof @cnnidpolitik and @cnnindonesia. Data collection is carried out purposively through documentationtechniques including the collection of screenshots of the comment column. The data collection stagewith the free reading technique is proficient, and continued with the data recording technique of a sentence that contains a maxim of quantity inconsistency. The results of the study show that non-compliance with the maxim of quantity occurs in the form of information that is too brief, excessive, and irrelevant. The main factors that cause this discrepancy include a lack of awareness of the principles ofeffective communication, emotional influence, and a lack of moderation in online discussions. This research contributes to the study of pragmatics and digital communication, as well as offers insights for media managers in improving the quality of interaction in the digital space.